A MODEL FOR CHINESE LANGUAGE LEARNING MANAGEMENT IN 21st CENTURY PRIVATE SCHOOLS IN SAMUT PRAKAN PROVINCE - Cai Liping; Anannawee, Paradee; Sittisomboon, Monasit (Journal of Educational Review Faculty of Education in MCU, 2022)
The objectives of this research were to evaluate and improve the performance of Chinese Language Learning Management in the 21st century of private schools in Samut Prakan province. The research divides into four processes: 1) To study environment and method in managing Chinese Language Learning in 21st Century for private schools in Samut Prakan province; 2) To improve Chinese Language Learning Management in 21st Century for private schools in Samut Prakan province; 3) To evaluate the third process; 4) To implement the management system into the sample groups, which include Directors, Deputy Director of Academic Affairs, and Chinese teachers. The numbers of sample groups derive from Krejcie & Morgan's table, and the total number of 123 answerers is obtained by using Stratified Random Sampling. The research tools include questionnaires, interview forms, and satisfaction assessment forms. The data obtained were analyzed using basic statistics and content analysis. The result shows that 1) The overall Chinese Language Learning Management in 21st Century for private schools in Samut Prakan province is at a high level and 2) The result of the model development has two components. The first component consists of 8 aspects: (1) Chinese language curriculum, (2) Learning activity management, (3) Measurement and evaluation, (4) Learning media/innovative information technology, (5) Organizing learning resources, (6) Organizing learning atmosphere, (7) Developing thinking skills and the integration of knowledge into use, and (8) promotion of relations with the Chinese Teachers Association of each region. Next, the second model development component is the factors promoting Chinese learning management in the 21 st century. They are (1) teacher leadership development, (2) thinking skills for the future, (3) learning innovations, (4) developing professional teachers, and (5) competence satisfaction of the stakeholders and users' satisfaction with the management. Overall, the result is very high, and the model is feasible and valuable at the highest level.